Correlation of serum prostate-specific antigen with Gleason score and Gleason grade group in patients with prostate adenocarcinoma at a tertiary care hospital (Journal of Pathology of Nepal, 2025)
Background: Prostate cancer is the most frequently diagnosed cancer among men, with the highest incidence seen in western countries. Prostate-specific antigen (PSA) is widely used as a screening tool for the detection of prostate cancer. Gleason grading system is the most commonly used pathological grading system for prostate cancer. This system is also a powerful prognostic factor and helps in determining clinical outcome.Materials and Methods: A retrospective cross-sectional study was done in the Department of Pathology, Tribhuvan University Teaching Hospital from January 2023 to June 2024. A total of 56 histopathologically and/or immunohistochemically confirmed cases of prostate adenocarcinoma with documented serum PSA level, Gleason score and Grade were included in the study. Serum PSA level was compared with Gleason score and Gleason grade. Correlation was done using Spearman’s rank correlation coefficient. P-value of ≤0.05 was considered to be statistically significant.Results: The mean age of the patients was 70.9 years with a mean serum PSA of 55.6 ng/ml. 63% of the patients had serum PSA level above 20 ng/ml. The most common Gleason score was 9. Gleason grade 5 was the most common Gleason grade. Statistically significant correlation of serum PSA with Gleason score and Grade was established with p-value